Evaluating and financing research: a comparison among universities in Italy, France, Germany and Spain (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2016)
This work focuses on evaluating and financing university research, a theme in the foreground in the public policy agendas of most European countries, through the analysis of four national contexts: Italy, France, Spain and Germany, whose university systems are mainly public and publicly financed. The study is articulated in two level of analysis. At the macro level, a survey has been administered to collect the opinions of the academic world in the four countries on crucial issues concerning funding and evaluating university research. At the micro level, the project analyses five public universities, in order to explain the factors that favor, in each of them, the production of excellent results in research. The case studies show that some crucial factors, such as the availability of economic resources and the characteristics of the urban and national contexts, are so different to render unsound any comparison of results that doesn’t take into consideration such uneven starting points. On the other hand, the study shows that, even in difficult times, universities are able to implement internal policies, such as well-structured research evaluation systems, that act as “favorable winds” facilitating their navigation towards the desired shores.